Synthesis of novel thiazolidinone bearing acridin-9-one moiety as antimicrobial agents - PANKAJ BABOO,; S.K.GUPTA, (International Journal of Pharma and Bio Sciences, 2017)
To synthesize some novel thiazolidinone bearing acridinone moiety by using various aromatic aldehydes. The newly synthesized compounds were screened for microbiological screening. A series of 5-arylidene-3-(2-phenyl-4-oxo-1,3-thiazolidine) acetohydrazido acridin-9-one have been synthesized via condensation of 3-(2-phenyl-4-oxo-1,3-thiazolidine) acetamido acridin-9-one with various aromatic aldehyde. These compounds confirmed by physical (TLC and M.P.) and spectral data (IR, NMR and MASS) and were subjected to microbiological screening viz antibacterial and antifungal activity. All the synthesized compounds proved to have potent antimicrobial activity against Gram positive, Gram negative and Fungal organism.